Considérations sur la nature, le rôle et l'influence de la doctrine en droit du travail au Québec - Jobin, Carol (Les Cahiers de droit)

(untitled) (Faculté de droit de l’Université Laval, 1985)
Considerations on the nature, role and influence of authoritative writings or doctrine in Québec labour law. Authoritative writings or « doctrine » may be defined as follows : « the aggregate of writings that constitute a source of law inasmuch as they may affect law through the actions of the courts or the legislator ». The following hypothesis may then be formulated : although everything points towards an increased development of such writings or doctrine in labour law, several factors have retarded this development. The needs for such research is illustrated via various examples. These needs can be felt in legislative circles, for instance, concerning questions raised over the present consultative committee on labour created by the Québec government for revising the Labour Code. The same applies to the courts in, for example, recent decisions on basic principles applying to collective labour relationships. The article also summarily describes various obstacles hindering the development of authoritative writings which may be divided into objective ones (i.e., recent law, uneven development viz-à-viz North American laws, widespread jurisdictions, lack of researchers, constraints on the university milieu) and subjective ones (i.e., lack of openness in the labour relations milieu, an idealized conception of what doctrine is all about and the knack researchers have for taking on activities linked to practice). Lastly, several desirable orientations for research are mapped out: the penetration of law in labour relations (« juridicisation ») and the invasion of adjudication (« judiciarisation »), the empirical effects of labour law and an integrated and comparative history of Québec labour laws.